COVID-19 Impacts on Christian and Muslim Organizations in Germany: A Comparative Mixed Methods Study - Klie, Anna Wiebke (Review of religious research, 2023)
The COVID-19 pandemic profoundly influenced all areas of life and day-to-day operations. This paper studies the impact of the pandemic on Muslim and Christian organizations in Germany. The focus is activity implementation, time investment, staff changes, and working processes of full-time staff and volunteers. On the basis of a quantitative survey (n = 454) and qualitative in-depth interviews with organizational representatives from 2021 to 2022 (n = 31), we follow a convergent, parallel mixed methods design to understand pandemic-related work changes, key challenges, and crisis management. Our quantitative analysis reveals differences in the activity performances in Muslim and Christian organizations both before and since the pandemic outbreak. While the monthly time investment of volunteers dropped significantly in Christian organizations during the pandemic, the working time of employees increased significantly in Muslim organizations. The qualitative analysis reveals distinct impacts on work processes and workloads in the organizations. Differences are due to organizational legal statuses, internal conditions, and different activity foci. Overall, our study indicates that religious organizations and their staff are resilient and adaptable. It contributes comparative data on faith-based organizations in Germany and highlights their important role in civil society. For future research, we recommend cross-national comparative studies.